NILAI-NILAI PENDIDIKAN DALAM BUDAYA ZIKIR NAZAMDI KABUPATEN SAMBAS - Suhari Suhari (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
The purpose of this study is to describe the educational values ​​within the dhikr nazam (recitation of the zikir) culture in Sambas Regency. This is because the dhikr nazam culture in the Malay community of Sambas Regency has been passed down from generation to generation. Currently, dhikr nazam has become prominent in wedding ceremonies, including aqiqah (aqiqah). The research method used by the researcher is descriptive. In descriptive research, the researcher develops concepts and gathers a description of the problem based on the facts. The subjects of this study are Malays who actively attend invitations and enjoy dhikr. The results conclude that the educational values ​​within the dhikr nazam culture of Sambas Regency are a traditional practice in Sambas Malay weddings. The Sambas Malay community carries out this tradition by holding the Majelis Walimatul Ursy (Assembly of Religious Gatherings), which includes traditional events and rituals, such as the recitation of dhikr nazam and dhikr al-barzanji in an area called Tarup. From the perspective of educational values ​​within the culture of dhikr nazam in Sambas Regency, several aspects are identified, such as religion, faith, morals, and worship. The main aspects of dhikr nazam are the preservation of the culture of the Malay community in Sambas Regency. Cultural preservation is evident, among other things, in the musical instruments used. Aspects of dhikr nazam include music and the purpose, function, and objective of dhikr nazam. This is linked to local wisdom, making it a highly engaging cultural practice.